Influences of polarity and hydration cycles on imbibition hysteresis in silica nanochannels. Issue 1 (6th December 2017) - Kelly, Shaina; Torres-Verdín, Carlos; Balhoff, Matthew T.
Abstract : Liquid imbibition experiments in 2D silica nanochannels reveal insights into the impact of hydrophilicity and liquid polarity on the hydrodynamic "no slip" boundary condition and nanoscale imbibition behavior. Abstract : Spontaneous liquid imbibition is a dominant mechanism for moving fluids in confinements with extremely high hydrodynamic resistance; i.e. nanopores. We demonstrate the impact of hydrophilicity and liquid polarity on nanoscale imbibition with dynamic measurements of the uptake of water–isopropanol (polar) and heptane (nonpolar) within 2D glass–silica nanochannels exposed to varied drying conditions and rehydration (rehydroxylation) cycles. The Lucas–Washburn equation, which does not consider interfacial fluidity effects, predicts that water–IPA and heptane should imbibe at similar speeds. However, we observed stymied and hysteretic water–IPA imbibition trends explained by extremely large contact line friction and increased effective viscosity, both surface chemistry-dependent, whereupon the results match a modified version of the Lucas–Washburn equation that accounts for dynamic wetting. In contrast, heptane imbibition, though still slower than the Lucas–Washburn equation prediction, was fairly insensitive to drying history and an order of magnitude faster than the polar mixture. The imbibition of aqueous solutions in analogous siliceous nanoporous materials and structures, ubiquitous in earth science and nanotechnology, may also be subject to hysteretic and large energy dissipation at contact lines and interfaces on account of hydrophilicity.